Exploring the Use of L1 in CLIL - Papaja, Katarzyna (Glottodidactica, 2007)
There have always been contradicting views about whether to use the mother tongue in the foreign language classroom. The issue this paper is going to examine in more detail is the use as well as the purpose of the Polish language used in selected Content and Language Integrated Learning classrooms.